Co-Treatment of Limonitic Laterites and Sulphur-Bearing Materials as an Alternative to the HPAL Process (The Minerals, Metals and Materials Society, 2004)
The high pressure acid leach process (HPAL) is being commercially used in four plants around the world to treat limonitic laterites. The two major operating costs of the HPAL process are the sulphuric acid and the energy required to heat the pulp to the desired temperature (>240°C). As an alternative to acid injection and steam heating, the in-situ generation of sulphuric acid and heat, produced during the high temperature pressure oxidation of sulphur-bearing materials blended with laterites, has been investigated at the laboratory scale. Various sources of sulphur have been examined, in particular, elemental sulphur, pyrrhotite and a Cu-Ni low-grade bulk concentrate. Under the proper blend ratios, all sulphur sources tested generated sufficient acid to result in equivalent nickel and cobalt dissolutions. A significant improvement to the process economics can result from the addition of sulphur sources containing valuable by-products, such as nickellcobalt andlor precious metals (gold and PGMs). This is especially true in the latter case, when the HPAL can be operated under Platsol conditions (i.e. with the addition of 5-10g/L of chloride), to dissolve the base metals and precious metals simultaneously in the autoclave. Various examples of the application of this concept are presented, together with a brief discussion of its implication on the autoclave design and the downstream processes to recover the values from the leach solutions. Keywords: limonite, co-treatment, acid consumption, sulphur, sulphur compounds, pressure acid leach (HPAL, PAL), Platsol process